2020
DOI: 10.1021/acs.jnatprod.9b01019
|View full text |Cite
|
Sign up to set email alerts
|

Pagoamide A, a Cyclic Depsipeptide Isolated from a Cultured Marine Chlorophyte, Derbesia sp., Using MS/MS-Based Molecular Networking

Abstract: A thiazole-containing cyclic depsipeptide with 11 amino acid residues, named pagoamide A (1), was isolated from laboratory cultures of a marine Chlorophyte, Derbesia sp. This green algal sample was collected from America Samoa, and pagoamide A was isolated using guidance by MS/MSbased molecular networking. Cultures were grown in a lightand temperature-controlled environment and harvested after several months of growth. The planar structure of pagoamide A (1) was characterized by detailed 1D and 2D NMR experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
(122 reference statements)
1
12
0
Order By: Relevance
“…This approach, coupled with approaches such as molecular networking, has been utilised in drug discovery, including the discovery of tutuilamides A–C, from a marine cyanobacterium, with potent elastase inhibition (IC 50 1–5 nM) and anticancer activity against lung H-460 cells [ 17 ]. Comparative metabolomics using the Global Natural Products Social (GNPS) molecular networking [ 18 ] platform led to the discovery of several new metabolites from cyanobacteria and microalgae, including yuvalamide A [ 19 ], pagoamide A [ 20 ], and palstimolide A, which exhibited strong anti-parasitic activity (IC 50 of 223 nM against malaria and 4.67 μM against leishmaniasis) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach, coupled with approaches such as molecular networking, has been utilised in drug discovery, including the discovery of tutuilamides A–C, from a marine cyanobacterium, with potent elastase inhibition (IC 50 1–5 nM) and anticancer activity against lung H-460 cells [ 17 ]. Comparative metabolomics using the Global Natural Products Social (GNPS) molecular networking [ 18 ] platform led to the discovery of several new metabolites from cyanobacteria and microalgae, including yuvalamide A [ 19 ], pagoamide A [ 20 ], and palstimolide A, which exhibited strong anti-parasitic activity (IC 50 of 223 nM against malaria and 4.67 μM against leishmaniasis) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optical rotation of the synthetic product 1 = +8.0 ( c 0.1, MeOH), was in close agreement with the value reported in the literature for natural pagoamide A = +5.5 ( c 0.1, MeOH). Spectral data, including 1 H-NMR, 13 C-NMR, were collected for both the natural and synthetic sample ( 1 ) and found to be in full agreement ( Table 2 ) [ 1 ], while the synthetic 1a showed remarkable discrepancies in spectral data as compared to natural pagoamide A, which unambiguously confirmed the original assignments of natural pagoamide A.…”
Section: Resultsmentioning
confidence: 73%
“…Very recently, Gerwick and co-workers described the structure of pagoamide A [ 1 ], a thiazole-containing cyclic depsipeptide isolated from the metabolites of a marine Chlorphyte, Derbesia sp., which was collected from the shallow coastal waters near American Samoa and cultured in the laboratory. Preliminary biological tests revealed that pagoamide A had no cytotoxicity against H-460 human lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The MS and MS/MS data of C. latifolia was subjected to MN analysis. The mass spectroscopic data were transformed into the mzXML format [59], and then processed on an online platform (http://gnps.ucsd.edu, accessed on 21 August 2019) according to a MN method [60]. The detailed metabolite information of the crude extract can be accessed via https://gnps.ucsd.edu/ProteoSAFe/libraries.jsp, accessed on 6 June 2021 and https://pubchem.ncbi.nlm.nih.gov/, accessed on 6 June 2021 (crude extract + references).…”
Section: Molecular Networking (Mn)mentioning
confidence: 99%